Effectiveness of commercial freshwater bathing as a treatment against amoebic gill disease in Atlantic salmon - Parsons, HJ; Barbara Nowak; Fisk, DM; Powell, M (2001)
Amoebic gill disease (AGD) is the most serious health problem in Atlantic salmon culture in Tasmania, Australia. This disease is caused by an amoeboid protozoan, Paramoeba pemaquidensis and has resulted in seacage mortalities as high as 50%. Current treatment involves fish being bathed in freshwater for periods of 2-3 h. The aim of this project was to determine the effectiveness of commercial freshwater bathing. Gill samples were collected from Atlantic salmon before and after routine freshwater bathing. Each fish was weighed, measured (fork length), gross AGD score determined, gill smears stained with "Diff Quick" and trypan blue and gill arches examined using routine histology. Freshwater bathing significantly reduced the prevalence of characteristic mucoid patches on the gills, presence of paramoebae on gill smears and the number of paramoebae per lesion in histological sections (P < 0.05). Trypan blue staining of gill smears revealed that 27% of the paramoebae were still alive after 2-h freshwater bathing, although the numbers appeared to be lower than before freshwater bathing. Paramoebae were commonly found (71.2%) in cysts formed by fused gill lamellae within AGD lesions. Before the bathing, only 31.9% of paramoebae were present within the cysts and the remaining parasites were present on the surface of the hyperplastic lesions. Results of this study showed that freshwater bathing is effective in the removal of the majority of paramoebae associated with fish infected with AGD. However, alterations in bathing procedure or an alternative treatment may be required to achieve the total removal of paramoebae from gills of Atlantic salmon. Â© 2001 Elsevier Science B.V.